Exploring Sociomathematical Norms Based on Students’ Interest in Mathematics Learning: A Qualitative Study at the Junior High School Level - Fitria, Afifah; Wilsher, Elijah (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to explore sociomathematical norms based on students’ interest in mathematics learning at the junior high school level, and to identify how different levels of learning interest influence students’ interaction, participation, and communication during mathematics learning activities. Methodology: This study used a descriptive qualitative approach with purposive sampling involving six students. Instruments included Likert-scale questionnaires, observation sheets, and semi-structured interview guidelines. Data were collected through observation, interviews, and questionnaires, and analyzed using the Miles and Huberman model with triangulation techniques. Main Findings: Students mostly show good sociomathematical norms, with the majority categorized at a moderate level of learning interest. Students with high interest demonstrate very good participation and communication, while those with moderate interest show consistent but less optimal interaction. Students with low interest tend to be passive and have difficulty expressing mathematical ideas clearly. Novelty/Originality of this study: This study integrates sociomathematical norms and learning interest in a single qualitative analysis, focusing on students’ real classroom behavior. It provides a deeper understanding of how different levels of interest shape interaction and communication, offering a more comprehensive perspective compared to previous studies that examined these aspects separately.